Implementation process using real UWB-RTLS - Bátori, Tamás; Tamás, Péter; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2026)
RTLS (Real Time Location System) is an absolutely booming, dynamically developing technology. Through my work, I have gained unique experience and knowledge that underpins the significance and relevance of this article. In Hungary, a few dozen implementations represent the RTLS market in 2025, which, in my opinion, is on the verge of a huge boom. I have already implemented RTLS technology in several projects, mostly in the production and service logistics systems of Tier 1 supplier companies. The operating systems have partially replaced the previously known barcode and radio frequency semi-automatic data collection devices and radio networks. In addition to using the installed UWB-based RTLS, we have achieved 99.99% operational accuracy and up to 20% resource savings compared to previous barcode-based Auto ID systems. Based on my 10 years of practical experience, I have concluded that it is necessary to conduct a feasibility study before every RTLS project in order to ensure that the project will be profitable. I have compiled an implementation process that assists with the implementation steps of RTLS projects and helps to prevent the risks that I have encountered over the past 10 years.